The Main Directions to Overcome the Challenges of the 21st Century in Agriculture - Garipov, Fanus Nagimovich; Gizatullin, Khamid Nurislamovich; Garipova, Zukhra Fanusovna (Economy of Regions, 2016)
In the article, on the basis of the world and national approaches to the solution of the food problem, the main vectors of the agricultural development aimed at overcoming the challenges of the XXI century and eventually attain the food independence of Russia are proved. The reasons for the decline per capita food production in the world are revealed; the increasing influence, in addition to the population growth, of the equalization of level and quality of food on its dynamics is noted. The dominant current public incentives form the growth rate of demand in advance the production. It is proposed to correct the strategy of agrarian development, while maintaining the principles of multiculturalism in the economy, focusing on the leading role of the large, vertically integrated business entities, and on the import substitution of the basic foodstuffs through the involvement of regional internal resources, including the development of cooperation principles, historically attended the emergence of commodity-money relations in the village. The growth of productivity of production factors is grounded as the main vector that may rectify the situation. It is recommended to diversify a set of cultivated plants and breeds of animals, as well as to develop a new commodity structure of production. 7he need for food imports is stressed in view of the fact that for the imported products, which are manufactured using primarily the renewable resources, Russia has to pay the price of the potential non-renewable natural resources, making it strategically disadvantageous. In order to achieve the sustainability of the basic parameters and enhance the results of the agricultural activity, it is recommended to use the tools of economic and mathematical modeling of the distribution of economic resources. The findings will be reflected in the justification of the strategy for the regional agricultural development.